The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea - Cho, Geonho; Inoue, Hiromitsu; Burckhardt, Daniel; Lee, Seunghwan (Zootaxa, 2016)
The records of the jumping plant-lice previously published under Carsidara shikokuensis (Miyatake, 1981) from Japan and C. marginalis Walker, 1869 from Korea are critically reviewed. It is concluded that both refer to the same species that is associated with Firmiana simplex (L.) W.Wight (Malvaceae). Carsidara shikokuensis shows no relevant morphological differences to C. limbata (Enderlein, 1926), and the two are synonymised: Carsidara limbata (Enderlein, 1926) = Carsidara shikokuensis (Miyatake, 1981) syn. nov. A record of C. marginalis from Korea is a misidentification of C. limbata. The latter is diagnosed and illustrated and differences to the former are discussed. The immatures of C. limbata are free-living on the leaves of Firmiana simplex and particularly the older instars secrete large amounts of flocculent wax and honeydew. Information on its potential usage as biological control agent of invasive Firmiana simplex in North America is briefly discussed.